Encapsulation of Lutein into Starch Nanoparticles to Improve Its Dispersity in Water and Enhance Stability of Chemical Oxidation. (21st December 2018) - Fu, Youjia; Yang, Jingde; Jiang, Longwei; Ren, Lili; Zhou, Jiang
Abstract : Lutein is a carotenoid and has important physiological and antioxidant activity, but its poor dispersity in water and ease of oxidation impede applications. In this paper, encapsulation of lutein into starch nanoparticles is achieved by preparing starch‐lutein nanoparticles via nanoprecipitation. Lutein content in the nanoparticles reaches 13.2 mg g −1 when 90 mg lutein is added into 50 mL 1% (w/v) starch paste. Starch‐lutein nanoparticles provide preservation for lutein from chemical oxidation so that the lutein in starch‐nanoparticles oxidizes with a speed only about 25% when compared to pure lutein. In addition, the dispersity of lutein in water was considerably improved, and the aqueous dispersion of the starch‐lutein nanoparticles can remain stable for 30 days. X‐ray diffraction analysis suggests that lutein might form a complex with amylose. Abstract : Lutein's shortcomings, poor dispersity in water, and stability of oxidation, impede its applications. These drawbacks have been remedied through encapsulation of lutein into starch nanoparticles via nanoprecipitation.